Classification and shear strength of soil in an Educational Institution (LACCEI, 2024)
Research conducted in an educational institution, the objective was to determine the relationship between soil classification and shear strength. For this purpose, a non-experimental cross-sectional design, correlational scope was used the population and sample was the soil the data collection techniques used were documentary review, interview and observation descriptive and inferential statistics were used in the data analysis. The problem is the deficiencies present in the pavilions and slabs such as fissures, cracks and sinking, which has been harming the students before the pandemic. A low plasticity sandy clay soil (CL) was obtained, ∅=19.311+0.203*LP with r2=0.874 and ε=0.073, and c=-0.768+0.576*γm with r2=0.921 and ε=0.004 according to SPSS software. It is concluded that the existing relationship between the classification and shear strength of the soil in the I.E. 80140 "J.F.S.C." was determined, and a Dashboard of soil shear strength was created, which will allow future projects to have better foundation designs and optimize costs in it.